Multifocal tDCS targeting lower-limb cortical areas preserves late-stage endurance and tunes phase-specific coordination during incremental cycling - Liang, Zhiqiang; Ramasawmy, Perianen; Guo, Xue; Fang, Yufei; Antal, Andrea; Liu, Yu (Frontiers in Physiology, 2025)
BackgroundMultifocal transcranial direct current stimulation (m-tDCS) may modulate distributed motor networks in a polarity-dependent and task-state-dependent manner to support performance near exhaustion. To this end, this study aims to test whether m-tDCS targeting lower-limb-specific cortical areas could optimize late-stage performance and phase-specific muscle coordination during cycling.MethodsTwo independent trials were conducted: (i) a tolerability assessment (Trial 1) and (ii) a randomized, double-blind, sham-controlled parallel study (Trial 2). In Trial 1, participants completed the tolerability test and recorded pain and side effects during a 21-min stimulation period. In Trial 2, healthy adults completed an incremental cycling test; late-stage performance was operationalized a priori as the 85%–100% peak power output (PPO) phase, during which the time-to-exhaustion (TTE), work (W), mean power (P), revolutions per minute (RPM), heart rate (HR), blood lactate level (ΔL), ratings of perceived exertion (RPE), and EMG-derived muscle contribution ratio (MCR) and knee co-activation index (CAI) were analyzed across propulsion and pull.Results(1) m-tDCS was well-tolerated; pain ratings declined progressively across the stimulation, with typical transient sensations. (2) At the 85%–100% PPO phase, m-tDCS increased W and RPM relative to sham without altering the mean power or ΔL; HR decreased after m-tDCS, and RPE rose only after sham. (3) At the coordination level, m-tDCS preserved quadriceps MCR during propulsion and reduced antagonistic activation during pull to prevent the CAI increase observed in the sham.Conclusionm-tDCS did not augment peak mechanical output but preserved late-stage endurance via phase-specific coordination tuning, which is consistent with improved neural efficiency near exhaustion. These findings refine mechanistic interpretations of the effects of tDCS on endurance and support m-tDCS as a safe, coordination-centric adjunct for high-intensity cycling.